2023
DOI: 10.1155/2023/8261279
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Scale Optimization of Hemp Seed Roasting Temperature and Time for Producing a High-Quality Pressed Oil

Abstract: Roasting is widely applied in oil processing to improve the extraction yield and desired sensory characteristics. The current study is aimed at optimizing roasting conditions (time and temperature) of hemp (Cannabis sativa L.) seeds prior to seed pressing to improve the oil yield and antioxidant capacity, using response surface methodology based on central composite design (CCD). Hemp seeds were roasted at five temperatures (132, 140, 160, 180, and 188°C) and for five duration times (9, 15, 30, 45, and 51 min)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Based on this, it can be concluded that their use to change color will be most justified, but in strictly controlled doses. Figure 1b shows that the mass of added bleaching earth is crucial in determining the effectiveness of color change in the CIE-Lab method, which is further confirmed by the work of Marrakchi et al [40] Doses of 2.5% by mass of BE5, BE6, and According to the work of Mansouri et al [43] and Tura et al [44] the initial content of natural dyes depends mainly on the hemp variety and pressing temperature. Moreover, increasing the processing temperature improves the solubility of chlorophylls and carotenoids in oils, which makes their removal more difficult.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Based on this, it can be concluded that their use to change color will be most justified, but in strictly controlled doses. Figure 1b shows that the mass of added bleaching earth is crucial in determining the effectiveness of color change in the CIE-Lab method, which is further confirmed by the work of Marrakchi et al [40] Doses of 2.5% by mass of BE5, BE6, and According to the work of Mansouri et al [43] and Tura et al [44] the initial content of natural dyes depends mainly on the hemp variety and pressing temperature. Moreover, increasing the processing temperature improves the solubility of chlorophylls and carotenoids in oils, which makes their removal more difficult.…”
Section: Resultssupporting
confidence: 57%
“…BE7 had the most effective impact on the tested samples; the impacts of BE1 and BE2 were slightly lower, and BE5 and BE6 also had a considerable impact (Figure 2a). The remaining BEs did not significantly According to the work of Mansouri et al [43] and Tura et al [44] the initial content of natural dyes depends mainly on the hemp variety and pressing temperature. Moreover, increasing the processing temperature improves the solubility of chlorophylls and carotenoids in oils, which makes their removal more difficult.…”
Section: Resultsmentioning
confidence: 92%
“…The pyrazines detected in this study, including 2,5-dimethylpyrazine, 2,5-diethyl-3-methylpyrazine, and 2-ethyl-3,5-dimethylpyrazine, are known to be the aromas detected in roasted sunflower seeds, pumpkin seeds, and almonds( Mansouri et al, 2023 ). In particular, 2-ethyl-3,5-dimethylpyrazine exhibited values above the threshold and is believed to be the aroma of roasted hemp seeds( Mansouri et al, 2023 ), also exhibited the highest odor activity in this study and is believed to be the major odor active compound. The p-cymene, which was found to be responsible for the overall scent of the raw, is known to be one of the volatile compounds of the important terpenes found in Cannabis( Srivastava & Singh, 2019 ).…”
Section: Resultsmentioning
confidence: 86%
“…The terpenes found in the highest concentration in hemp seed oil, which are considered key contributors to the unique aroma with odor activity values, are presented in Table 4. Studies have highlighted that terpenes in hemp seed oil play significant roles in protecting it against oxidative stress [19], due to their ability to scavenge free radicals [73]. Furthermore, research suggests terpenes can enhance well-being within a healthy lifestyle.…”
Section: Terpenesmentioning
confidence: 99%